2020
DOI: 10.1093/nop/npz071
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcomes on Head Start III: a prospective, multi-institutional clinical trial for young children diagnosed with malignant brain tumors

Abstract: Background Current pediatric brain tumor treatment focuses on titrating toxicity based on risk factors while simultaneously improving survivorship. The Head Start (HS) protocols I to IV (1991-present) use high-dose chemotherapy (HDCTx) with an aim of reducing or eliminating cranial irradiation in very young children, the most vulnerable to its effects. Methods We examined estimated Full Scale IQ, overall Adaptive Functioning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Twenty-four patients (56%) had MB and 12 (28%) received radiation therapy. As a group, the Headstart III patients per-formed within average to low-average range across all tested variables and no significant difference were found by diagnosis (MB, PNET and others) [45]. Fay McClymont et al, also reported the neurocognitive profile of 24 survivors of MB treated with HDC according to the protocol 99703.…”
Section: Neurocognitive Outcomementioning
confidence: 97%
“…Twenty-four patients (56%) had MB and 12 (28%) received radiation therapy. As a group, the Headstart III patients per-formed within average to low-average range across all tested variables and no significant difference were found by diagnosis (MB, PNET and others) [45]. Fay McClymont et al, also reported the neurocognitive profile of 24 survivors of MB treated with HDC according to the protocol 99703.…”
Section: Neurocognitive Outcomementioning
confidence: 97%
“…For these reasons, cognitive and neuropsychological outcomes have been included as endpoints in recent trials with the aim of reducing or eliminating radiotherapy, when possible, without affecting prognosis. Headstart trials focused on intensive chemotherapy followed by hematopoietic stem cell rescue with the goal of avoiding or postponing radiotherapy; results published from Headstart II and III showed stable neuro-cognitive functioning over time, suggesting this approach to be effective in sparing CNS development in young children [ 74 ].…”
Section: Factors Influencing Neurologic and Cognitive Outcomesmentioning
confidence: 99%
“…Cranial radiation therapy (CRT) is often identified as the most impactful and deleterious treatment-related risk factor to neurocognitive outcomes for PBT survivors due to white matter changes that associate with neurocognitive dysfunction and persisting late effects [ 21 ]. Chemotherapy, while thought to be less toxic relative to radiation treatment, has been associated with cognitive impairment [ 22 , 23 ], as well as hearing impairments [ 24 ] thus, magnifying the functional impact of neurocognitive late effects. Independent of other treatment modalities, neurosurgical resection of tumors is associated with neurocognitive morbidity [ 25 , 26 ] and in some cases results in the post-surgical complication of posterior fossa syndrome (also known as cerebellar mutism) characterized by diminished speech, ataxia, emotional and behavior lability, and apathy [ 27 ] which may lead to worse long term neurocognitive outcomes for PBT survivors [ 28 ].…”
Section: Educational Pain Points For Pediatric Brain Tumor Survivorsmentioning
confidence: 99%